A Terrible Thing to Waste : Arthur Fletcher and the Conundrum of the Black Republican - Golland, David Hamilton (Book collections on Project MUSE., 2019)
"Arthur Allen Fletcher was the most important civil rights leader you've (probably) never heard of. Although this Kansan's name appears in books on affirmative action, the United Negro College Fund, and in the recent and growing scholarship on Black Republicans, the story of the man who coined the phrase "A Mind Is a Terrible Thing to Waste" has been left out of standard treatments on the civil rights era. The life of Arthur Fletcher represents the triumph, tragedy, and conundrum of the postwar Black Republican. In 1946, when he returned home to Kansas after World War II, the Republican Party was "the Party of Lincoln," a big tent truly welcoming of African Americans. Its 1960 presidential platform was stronger on civil rights than that of the Democrats. But New Movement Conservatism and Nixon's Southern Strategy steadily alienated Black voters even as candidates like Ronald Reagan used coded racist language to appeal to unreconstructed white Southerners and the Northern white working class. Whereas Fletcher could triumphantly implement affirmative action during the early Nixon administration, his ability to promote civil rights policy tragically eroded in the following decades. Today, African Americans who are right-of-center on issues other than race relations face a conundrum: support the Democrats with whom they agree on civil rights but little else, or stick with a Republican Party from which they have been alienated. A Terrible Thing to Waste is the first biography of Fletcher. The book traces his life from his origins in Kansas in the 1920s to his death in 2005, still committed to his ideals but angry about American racism and exhausted by a Party that wanted to reverse his achievements"--